The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/dna4010002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Particle LET and Fluence on the Complexity and Frequency of Clustered DNA Damage

Mohammad Rezaee,
Amitava Adhikary

Abstract: Motivation: Clustered DNA-lesions are predominantly induced by ionizing radiation, particularly by high-LET particles, and considered as lethal damage. Quantification of this specific type of damage as a function of radiation parameters such as LET, dose rate, dose, and particle type can be informative for the prediction of biological outcome in radiobiological studies. This study investigated the induction and complexity of clustered DNA damage for three different types of particles at an LET range of 0.5–250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Photon radiation with low LET (X-rays, beta, or γ-rays, <10 keV/µm) means a homogeneous energy deposition in the entire tissue volume. In contrast, high LET radiation (protons, alpha particles, and neutrons, >10 keV/µm) decelerates faster than photons, resulting in the formation of a fast Bragg peak, which produces a low entrance dose with a greater depth of tissue penetration that increases with radiation energy [29]. A wide range of DNA lesions can occur during radiation treatment.…”
Section: Consequences Of Ionizing Radiation To the Human Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Photon radiation with low LET (X-rays, beta, or γ-rays, <10 keV/µm) means a homogeneous energy deposition in the entire tissue volume. In contrast, high LET radiation (protons, alpha particles, and neutrons, >10 keV/µm) decelerates faster than photons, resulting in the formation of a fast Bragg peak, which produces a low entrance dose with a greater depth of tissue penetration that increases with radiation energy [29]. A wide range of DNA lesions can occur during radiation treatment.…”
Section: Consequences Of Ionizing Radiation To the Human Bodymentioning
confidence: 99%
“…Approximately two-thirds of radiation-induced DNA damage is caused by the indirect effects of reactive oxygen species (ROS) [40]. High-LET radiation is more lethal than comparable doses of low-LET radiation due to a condensed energy deposition pattern and a very dense ionization pattern that causes potentially lethal DNA damage [29].…”
Section: Consequences Of Ionizing Radiation To the Human Bodymentioning
confidence: 99%
“…There are multiple studies pointing out that irradiations with different types of particles (i.e., species, energy and linear energy transfer (LET) of particles) induce different kinds of DNA damage (64,65) with different levels of complexity (i.e., different types of DNA lesions in the same DNA region) and clustering (i.e., accumulation of DNA damage in the same DNA region) (66,67). Apart from DNA lesions directly induced by direct interaction with the DNA molecule, ionizing radiation (IR) also creates reactive species (i.e., reactive oxygen or nitrogen species, ROS or RNS) by interacting with other molecules, such as water, proteins, etc… (68)(69)(70), which then also contribute to further formation of DNA damage within irradiated cells.…”
Section: Hr Is Implicated Sooner In the Processing Of Dna Lesions Ind...mentioning
confidence: 99%
“…Apart from DNA lesions directly induced by direct interaction with the DNA molecule, ionizing radiation (IR) also creates reactive species (i.e., reactive oxygen or nitrogen species, ROS or RNS) by interacting with other molecules, such as water, proteins, etc… (68)(69)(70), which then also contribute to further formation of DNA damage within irradiated cells. Computational approaches (66,67) showed that irradiations with α-particles lead to a small number of DNA damage sites with concentrated clusters of complex DNA lesions compared to irradiations with protons, which give a higher number of DNA damage sites containing less clusters of complex DNA lesions. Here, with the use of the MIRCOM ion microbeam, we induce, whatever the particle delivered, protons or α-particles, DNA lesions within a very localized subnuclear area, thus potentially more clustered.…”
Section: Hr Is Implicated Sooner In the Processing Of Dna Lesions Ind...mentioning
confidence: 99%
“…In addition to isolated single DNA lesions, single-and double-strand breaks, and apurinic/apyrimidinic sites, formation of clustered DNA lesions within a short stretch of DNA is a well-established characteristic of ionizing radiation [4][5][6][7][8][9]. For the sake of convenience, MDS have been defined as two or more lesions within ~20 base pairs, of which tandem lesions, with damage to two contiguous bases, constitute an important fraction [7,[10][11][12]. Generation of radicals by metal ions also results in MDS [13,14].…”
Section: Introductionmentioning
confidence: 99%